Palladium-catalyzed substitution of (coumarinyl)methyl acetates with C-, N-, and S-nucleophiles - Chattopadhyay, Kalicharan; Fenster, Erik; Grenning, Alexander J.; Tunge, Jon A. (Beilstein Journal of Organic Chemistry, 2012)
The palladium-catalyzed nucleophilic substitution of (coumarinyl)methyl acetates is described. The reaction proceeds though a palladium π-benzyl-like complex and allows for many different types of C-, N-, and S-nucleophiles to be regioselectively added to the biologically active coumarin motif. This new method was utilized to prepare a 128-membered library of aminated coumarins for biological screening.
Keywords: benzylation; catalysis; coumarin; chemical diversity; decarboxylative; palladium; substitution